Sustainable Agritourism Development in Romania’s North-West Mountain Region: A TOPSIS-Based Evaluation of Strategic Priorities - Alina Emilia Maria Gherdan; Ramona Vasilica Bacter; Ramona Ciolac; Tiberiu Iancu; Cristina Maria Maerescu; Monica Angelica Dodu; Aurelia Ioana Chereji; Vasile Grigore Herman; Alexandra Ungureanu; Denis Paul Bacter (Agriculture)
Rural tourism and agritourism are essential drivers of sustainable economic development in mountain regions, generating income opportunities while preserving cultural and natural heritage. The North-West region of Romania has significant potential in this sector. Yet, tourism development is unevenly distributed, and the integration of local economic activities remains limited, an imbalance that reduces the overall impact of tourism on regional sustainability and economic resilience. To assess viable strategies for agritourism development, the study applies the TOPSIS method, evaluating four key criteria: infrastructure accessibility, diversity of tourism experiences, service quality, and long-term economic sustainability. A survey was conducted with 102 respondents, and the collected data were analyzed using the TOPSIS framework to determine the most effective development approaches. The findings indicated that the ecotourism trails represent the most favorable strategy (Ci = 0.678), followed by promoting local products within tourism (Ci = 0.602) and expanding rural guesthouses (Ci = 0.467). In contrast, integrated tourism packages and tourist information centers ranked lower, suggesting that infrastructure investment and the strategic use of local resources should be prioritized. These insights provide practical recommendations for policymakers, investors, and local stakeholders, emphasizing the need for targeted support in ecotourism and rural economic initiatives. Furthermore, the study contributes to academic research by offering a structured, replicable approach to evaluating rural tourism development. By highlighting sustainable investment directions, the findings support efforts to enhance Romania’s rural tourism competitiveness while fostering economic growth in mountain regions.